CCN3 Signaling Is Differently Regulated in Placental Diseases Preeclampsia and Abnormally Invasive Placenta - Duan, Liyan; Schimmelmann, Manuela; Wu, Yuqing; Reisch, Beatrix; Faas, Marijke; Kimmig, Rainer; Winterhager, Elke; Köninger, Angela; Gellhaus, Alexandra (Frontiers in Endocrinology, 2020)
Objectives: An adequate development of the placenta includes trophoblast differentiation with the processes of trophoblast migration, invasion, cellular senescence and apoptosis which is crucial to establish a successful pregnancy. Altered placental development and function lead to placental diseases, such as preeclampsia (PE) which is mainly characterized by insufficient trophoblast invasion, and abnormally invasive placenta (AIP) disorders (Placenta accreta, increta or percreta) which are characterized by excessive trophoblast invasion. Both of them will cause maternal and fetal morbidity/mortality. However, the etiology of these diseases is still unclear. Our previous study has shown that the matricellular protein nephroblastoma overexpressed (NOV, CCN3) induces G0/G1 cell cycle arrest, drives trophoblast cells into senescence and activates FAK and Akt kinases resulting in reduced cell proliferation and enhanced migration capability of the human trophoblast cell line SGHPL-5. The present study focus on whether CCN3 can alter cell cycle-regulated pathways associated with trophoblast senescence and invasion activity in pathological versus gestational age-matched control placentas. Methods: Cell cycle regulator proteins were investigated by immunoblotting and qPCR. For localization of CCN3, p16, p21 and Cyclin D1 proteins co-immunohistochemistry was performed. Results: In early-onset PE placentas CCN3 was expressed at a significantly lower level compared to gestational age-matched controls. The decrease of CCN3 level is associated with an increase in p53, Cyclin E1 and pRb protein expression whereas the level of cleaved Notch-1, p21, Cyclin D1, pFAK, pAKT and pmTOR protein decreased. In term AIP placentas, the expression of CCN3 was significantly increased compared to matched term controls. This increase was correlated to an increase in p53, p16, p21, Cyclin D1, cleaved Notch-1, pFAK, pAkt and pmTOR whereas pRb was significantly decreased. However, in late PE and early AIP placentas no significant differences in CCN3, p16, p21, Cyclin D1, p53 and cleaved Notch-1 expression were found when matched to appropriate controls. Conclusions: CCN3 expression levels are correlated to markers of cell cycle arrest in an opposite way in PE and AIP by activating the FAK/AKT pathway in AIP, or downregulating in PE. This may be one mechanism to explain the different pathological features of placental diseases, PE and AIP.